NAVIGATING INSTITUTIONAL CHANGE: POLICY DIRECTION AND COMMITMENT TO ACCESSIBILITY SERVICES IN ISLAMIC HIGHER EDUCATION AFTER TRANSFORMATION - Bashori, Bashori; Lailisna, Novi Nur (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Background: This study explored and evaluated accessibility services at PTKIN (Perguruan Tinggi Keagamaan Islam Negeri or State Islamic Religious Universities) after institutional transformation. The vision of institutional change that is more universal and inclusive is one of the triggers to see the extent to which Islamic higher education institutions have realized their commitment to accessibility services. Purpose: This study had examined the policy and implementation of accessibility services in the aspects of policy, practice, and institutional culture at PTKIN, with the main focus on UIN Imam Bonjol Padang, which has undergone transformation from an institute to a university. Method: This study used a qualitative case study approach. UIN Imam Bonjol Padang as the object of research by considering aspects of the fulfillment of institutional transformation elements from institute to university. Data collection techniques were through interviews, observation, and document analysis. Result: The results of this study showed that the institutional transformation of PTKIN in this study has not been in line with the fulfillment of the accessibility rights of educational institutions. UIN Imam Bonjol Padang, as a case study, still shows a lack of concrete policies in accessibility services for students. The absence of specific policies and limited accessibility infrastructure are the main factors that hinder the fulfillment of educational rights for students with special needs. Conclusion: This study confirms that PTKIN needs to prioritize accessibility as part of its post-transformation institutional policy. The main recommendations in this study are the need for clearer and more implementable policies, the development of infrastructure that supports accessibility, and increasing the awareness of the academic community of the importance of inclusive education services. Thus, institutional transformation is not only a change in administrative status, but also reflects an increase in the quality of educational services for all without discrimination.